(±)-Quassidine K, a pair of cytotoxic bis-β-carboline alkaloid enantiomers from Picrasma quassioides. Issue 4 (16th February 2020) - Guo, Xin-Ming; Li, Fei; Zheng, Fang-Fang; Gong, Na-Na; Li, Yan; Feng, Wen-Zhou; Tian, Lin
Abstract: (±)-Quassidine K (1 ), a pair of new bis- β -carboline alkaloid enantiomers, were isolated from Picrasma quassioides . Their structures were determined on the basis of detailed spectroscopic data analysis. The absolute configurations of (+)- S -quassidine K (1a ) and (−)- R -quassidine K (1b ) were determined by comparing with the reported experimental ECD spectra after chiral separation. The cytotoxicity assay showed activity against HeLa cells with IC50 values of 15.8 and 20.1 μM, respectively. Graphical Abstract: